Kelemahan Pengaturan Konten Youtube Sebagai Agunan Kredit dan Implikasinya Terhadap Perlindungan Bank - Arif Budiman; Inda Rahadiyan (Fakultas Hukum Universitas Islam Indonesia, 2024)
This research analyzes the weaknesses in regulating YouTube content as collateral for banking credit in Indonesia. Apart from that, analyzing the implications for protection for banks as creditors. This research is a type of normative legal research with a statutory approach and a conceptual approach. The research results show that the credit collateral object is the weakness in regulating YouTube content. YouTube content cannot be assessed objectively because its characteristics are subjective and involve elements of the creator's creativity. Personal branding also influences building a creator's popularity, while this can be illustrated through the number of subscribers and viewers who can easily be purchased. Apart from that, collateral objects in the form of YouTube content are difficult to execute. YouTube content will be difficult to resell because there is no secondary market that can absorb these assets. YouTube content as credit collateral requires an assessment institution, such as Singapore, which has a special research institution for intellectual property, such as Baker McKenzie, Wong & Leow, and Consor Intellectual Asset Management. Government Regulation Number 24 of 2022 concerning Implementing Regulations of Law Number 24 of 2019 concerning the Creative Economy does not provide adequate legal protection for creditors. If YouTube content decreases in popularity or value, creditors will have difficulty selling the collateral. This will have an impact on the bank's health level, so banks must apply the principle of prudence in providing credit with collateral in the form of YouTube content.